Technical and tactical aspects that differentiate winning and losing performances in boxing - Ashker, S. E. (International Journal of Performance Analysis in Sport, 2011)
The analysis of video recordings of boxing matches could verify differentiation between winners and losers. The aim of this study was to determine aspects of winning and losing boxers based on the use of technical and tactical elements over the progression of boxing contests and differences through bouts. A Sample of 66 first-ranked male elite boxers (aged 22.1 ± 2.3) in 33 fights (11finals; 22 semi-finals) was used. Nineteen variables were determined to describe technical and tactical elements within boxing matches. Differences between rounds were examined by a combined 3 x 2 within and between factors ANOVA to identify main effects through rounds as within winners or losers, with Bonferroni post-hoc analysis. Results showed that winners were higher developed than losers in performing offensive skills directed to head or body, total, lead and rear hand punches, boxing combinations, defensive skills and technical performance effectiveness (TPE) statistics. Data emphasizes the significance of making more punches in both single punches and in combinations in order to score more points than the opponent. Defensive skills should be utilized by arm, foot and trunk connected with attack. Prospective studies need to be considered to investigate the association between performance and physiological and biomechanical variables.